Outcomes following Kidney transplantation in IgA nephropathy: a UNOS/OPTN analysis. (24th August 2015) - Kadiyala, Aditya; Mathew, Anna T.; Sachdeva, Mala; Sison, Cristina P.; Shah, Hitesh H.; Fishbane, Steven; Jhaveri, Kenar D.
Abstract: This study updates assessment of post‐transplant outcomes in IgAN patients in the modern era of immunosuppression. Using UNOS/OPTN data, patients ≥18 yr of age with first kidney transplant (1/1/1999 to 12/31/2008) were analyzed. Multivariable Cox regression models and propensity score‐based matching techniques were used to estimate hazard ratios (HRs) for death‐censored allograft survival (DCGS) and patient survival in IgAN compared to non‐IgAN. Results of multivariable regression were stratified by donor type (living vs. deceased). A total of 107, 747 recipients were included (4589 with IgAN and 103 158 with non‐IgAN). Adjusted HR for DCGS showed no significant difference between IgAN and non‐IgAN. IgAN had higher patient survival compared to non‐IgAN (HR 0.54, 95% CI 0.47–0.62, p < 0.0001 for deceased donors; HR 0.42, 95% CI 0.33–0.54, p < 0.0001 for living donors). Propensity score‐matched analysis was similar, with no significant difference in DCGS between matched groups and higher patient survival in IgAN patients compared to non‐IgAN group (HR 0.54, 95% CI 0.47, 0.63; p‐value <0.0001). IgAN patients with first kidney transplant have superior patient survival and similar graft survival compared to non‐IgAN recipients. Results can be used in prognostication and informed decision‐making about kidney transplantation in patients with IgAN.